Nanogap Dielectric Capacitor for Label Free Bio-Molecules Detection - Uda, Hashim, Prof. Dr.; Asmah, Mat Taib; Azizullah, Saifullah; Muhammad Emi, Azri Shohini; Thikra, S. Dhahi (Malaysian Invention and Design Society (MINDS), 2010)
Prof. Dr. Uda Hashim and his team won silver at 21st International Invention, Innovation and Technology Exhibition (ITEX) 2010, 14th - 16th May 2010 at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur, Malaysia.